Richard Ovenden, Burning the Books: A History of Knowledge Under Attack. London: John Murray (2020). Issue 1 (27th July 2022) - Brown, Katherine E
Abstract : Richard Ovenden, Burning the Books: A History of Knowledge Under Attack. London: John Murray (2020)